Near field communication(nfc) technology - Tokhtamysh, M. S. (ХНУРЕ, 2024)
Human communication has changed throughout history. Most methods of communication now use electromagnetic waves to carry information. One invention that revolutionized communication between devices was Near Field Communication (NFC), which uses a type of short-range radio wave. The work given offers a fundamental comprehension of the functioning of NFS technology. It also describes the differences in active and passive devices that participate in the data transfer process.